2020
DOI: 10.3390/cancers12123860
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Epidemic—The Underestimated Risk of Endometrial Cancer

Abstract: Endometrial cancer (EC) is the most frequently observed malignant gynecologic disease in developed countries. There is a strong association between the established risk factor obesity and the incidence of EC. Furthermore, the rate of women with a body mass index (BMI) > 30 kg/m2 is increasing worldwide, correspondingly leading to a higher prevalence of EC. Understanding the adipose tissue as an endocrine organ, elementary pathophysiological pathways of tumorigenesis have been revealed. This includes the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
0
12
0
1
Order By: Relevance
“…As the major risk factor for uterine neoplasms, obesity epidemic has become a global public health problem. 16 We report herein for the first time that weight loss interventions improve reproductive outcomes in women with early-stage EC and AH who underwent fertility-sparing treatment. Weight loss of ≥5% was an independent positive factor for pregnancy after adjustment for age at diagnosis, progestin treatment duration, and endometrial thickness.…”
Section: Discussionmentioning
confidence: 89%
“…As the major risk factor for uterine neoplasms, obesity epidemic has become a global public health problem. 16 We report herein for the first time that weight loss interventions improve reproductive outcomes in women with early-stage EC and AH who underwent fertility-sparing treatment. Weight loss of ≥5% was an independent positive factor for pregnancy after adjustment for age at diagnosis, progestin treatment duration, and endometrial thickness.…”
Section: Discussionmentioning
confidence: 89%
“…As the major risk factor for EC, obesity has become a global public health problem (13,14). According to the World Health Organization, obesity is defined as BMI ≥30 kg/m 2 (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depth of myometrial invasion, LVSI, and a Grade of 3 were found to be independent risk factors for those recurrence patients, which are consistent with the results of many current reports ( 19 , 21 ). In addition, some studies showed that obesity is an important risk factor for patients with EC ( 23 , 24 ). Although in this research, we found no evidence to support this.…”
Section: Discussionmentioning
confidence: 99%